2020
DOI: 10.18502/ijm.v12i6.5030
|View full text |Cite
|
Sign up to set email alerts
|

Using autochthonous Bdellovibrio as a predatory bacterium for reduction of Gram-negative pathogenic bacteria in urban wastewater and reuse it

Abstract: Background and Objectives: The microbial contamination of wastewater is associated with health risks. The aim of this study was to use the autochthonous Bdellovibrio potential to prey Gram-negative pathogenic bacteria as a bio-control agent to treat urban wastewater. Materials and Methods: Thirty-six raw sewage samples were collected for isolation of Bdellovibrio. Double layer plaque assay was used for isolation and the isolates were identified by microscopic examination and molecular analysis. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…BALO isolated from fishponds have been reported to contribute to fish health and growth performance, by reducing the incidence of diseases caused by Aeromonas hydrophila and V. alginolyticus 69 . Recent studies have attempted to control bacterial pathogens in aquaculture systems by using BALO cultures to increase their abundance in the rearing water 70 , 71 . However, some bioaugmentation strategies are thought to be ineffective due to the maladaptation of allochthonous inoculums to the new environment, where local abiotic conditions and the resident microbial community may impede their establishment and proliferation 72 , 73 .…”
Section: Resultsmentioning
confidence: 99%
“…BALO isolated from fishponds have been reported to contribute to fish health and growth performance, by reducing the incidence of diseases caused by Aeromonas hydrophila and V. alginolyticus 69 . Recent studies have attempted to control bacterial pathogens in aquaculture systems by using BALO cultures to increase their abundance in the rearing water 70 , 71 . However, some bioaugmentation strategies are thought to be ineffective due to the maladaptation of allochthonous inoculums to the new environment, where local abiotic conditions and the resident microbial community may impede their establishment and proliferation 72 , 73 .…”
Section: Resultsmentioning
confidence: 99%
“…The inability of other remaining Bdellovibrio species to prey on other host cells could also be due to its structural features, which inhibit attachment, penetration or replication or may be due to the escape strategy of the host cell, which is not studied in the present study. Recent studies demonstrated applications of Bdellovibrio strains in biological wastewater treatment for reducing the burden of Gram-negative bacteria (Wu et al 2019;Jafarian et al 2020).…”
Section: Discussionmentioning
confidence: 99%